2013
DOI: 10.1002/jgrg.20112
|View full text |Cite
|
Sign up to set email alerts
|

The implications of minimum stomatal conductance on modeling water flux in forest canopies

Abstract: [1] Stomatal conductance (g s ) models are widely used at a variety of scales to predict fluxes of mass and energy between vegetation and the atmosphere. Several g s models contain a parameter that specifies the minimum g s estimate (g 0 ). Sensitivity analyses with a canopy flux model (MAESTRA) identified g 0 to have the greatest influence on transpiration estimates (seasonal mean of 40%). A spatial analysis revealed the influence of g 0 to vary (30-80%) with the amount of light absorbed by the foliage and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 91 publications
(94 reference statements)
4
73
1
Order By: Relevance
“…Replacing these values with zeros had a large impact on predicted fluxes, particularly under high VPD conditions at the C4-dominated Howard Springs. This result agrees with a recent study by Barnard and Bauerle (2013), who concluded that g 0 was in fact the most sensitive parameter for correctly estimating transpiration fluxes. It is clear that further investigation is needed on the impact of different g 0 assumptions in land surface and ecosystem models.…”
Section: Minimum Stomatal Conductance Gsupporting
confidence: 93%
“…Replacing these values with zeros had a large impact on predicted fluxes, particularly under high VPD conditions at the C4-dominated Howard Springs. This result agrees with a recent study by Barnard and Bauerle (2013), who concluded that g 0 was in fact the most sensitive parameter for correctly estimating transpiration fluxes. It is clear that further investigation is needed on the impact of different g 0 assumptions in land surface and ecosystem models.…”
Section: Minimum Stomatal Conductance Gsupporting
confidence: 93%
“…In these low photosynthesis situations, g s is mostly driven by g 0. The high sensitivity to g 0 in the Eucalyptus plantation in this study supports the conclusions of Barnard and Bauerle (2013), who stressed the necessity of measuring g 0 accurately. An estimate of g 0 using linear extrapolation from stomatal conductance model regression underestimated the minimum stomatal conductance by more than 50% compared with direct measurements.…”
Section: Parameters Set Constant Across the Standsupporting
confidence: 88%
“…While high sensitivity to g 1 (the slope between the GPP and TR), as shown by Bauerle and Bowden (2011), was expected, the minimum stomatal conductance (g 0 ) had a greater effect on TR, LUE, and WUE. While g 0 has commonly been assumed to be close to zero with little effect on water fluxes (Caird et al 2007;Zeppel et al 2010), recent studies have shown that g 0 could be higher than previously expected in many ecosystems (Ogle et al 2012) and that its value could change seasonally (Barnard and Bauerle 2013). In a recent study using MAESTRA, it was shown that g 0 had a large effect on TR (Bowden and Bauerle 2008).…”
Section: Parameters Set Constant Across the Standmentioning
confidence: 97%
“…1). Conversely, b bb values reported in the literature are highly variable (1-400 mmol m −2 leaf s −1 in the survey by Barnard and Bauerle, 2013, for a broad range of plant species). In CLM4.0, the default b bb for C 3 plants is significantly smaller than in CLM4.5 (2 vs. 10 mmol m −2 leaf s −1 ) (Oleson et al, 2010).…”
Section: A9 Stomatal Conductancementioning
confidence: 80%